2021
DOI: 10.1002/ejlt.202100002
|View full text |Cite
|
Sign up to set email alerts
|

Development of Phospholipids Vesicular Nanocarrier for Topical Delivery of Tea Tree Oil in Management of Atopic Dermatitis Using BALB/c Mice Model

Abstract: This work aims to develop and evaluate the efficacy of tea tree oil (TTO) ethosomal cream with improved deposition in skin layers for treatment of atopic dermatitis (AD). Ethosomes of TTO are developed using phosphatidylcholine (2% and 3% w/v) and ethanol (20%, 30%, and 40% w/v). Ethosomes are evaluated for percent entrapment efficiency (%EE), vesicle size, zeta potential, and in vitro drug diffusion. Ethosomal creams with optimized ethosomal dispersion are developed and evaluated for physicochemical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The cream retained at greater extent in epidermis and dermis, decreased the clinical scores and inflammatory responses. It showed no cytotoxic effect on HaCat cell lines 62 …”
Section: Resultsmentioning
confidence: 97%
“…The cream retained at greater extent in epidermis and dermis, decreased the clinical scores and inflammatory responses. It showed no cytotoxic effect on HaCat cell lines 62 …”
Section: Resultsmentioning
confidence: 97%
“…However, since the hydrodynamic radius is generally larger than the actual physical radius (due to solvation effects), it can be stated that the data measured for all formulations are probably on the small side for micelles, and especially for the DMPC formulation exhibiting data much smaller than what would be expected for micelles. In contrast, according to the literature, in phospholipid/ethanol systems with higher content of water, vesicular systems are formed with much larger aggregate size (ranging from one to several orders of magnitude larger) [17,18].…”
Section: Physico-chemical Characterization Of Different Akvano Formul...mentioning
confidence: 89%
“…From the findings, it was observed that the prepared ethosomal cream deposited more in skin layers, was safe during cell line examination, and efficiently minimized inflammation through IgE antibodies, WBC, eosinophils infiltration, and a decreased clinical score as compared to a simple TTO cream. Hence, it has been approved as more efficacious for AD treatment . Three vesicular cyanocobalamin-loaded formulations, i.e., ethosomes, liposomes, and transferosomes, through a film-hydration technique were prepared with better permeation efficiency across skin layers for the scavenging activity against nitric oxide in pathological conditions of AD and psoriasis.…”
Section: Treatment Approaches For Various Disorders Using Topical Dru...mentioning
confidence: 99%